Rural women awards - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Seven of the 31 women awarded the 2001 global prizes for women s creativity in rural life work in Africa; prizes were scheduled for presentation in Geneva on 15 October World Rural Women s Day. Laureates include Joyce Vida Donkor (Ghana) for...